Dietary Omega-3 Polyunsaturated Fatty Acids and Cancer - Calviello, Gabriella; Serini, Simona; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Dietary Omega-3 Polyunsaturated Fatty Acids and Cancer provides all the latest information on the possible benefits of omega-3 polyunsaturated fatty acids (PUFAs) against a wide series of cancers. Several influential scientists in this field have contributed to make this book an unique one amongst the others published so far in this field. The chapters give detailed information about the results obtained in this field through experimental studies conducted on both animals and cultured cells, as well as through human intervention trials and epidemiological observational studies. This book represents an important tool for researchers working in nutrition and oncology, since it collects all the knowledge about omega-3 PUFAs and cancer, even the most recent, in a single publication. For the first time controversies among the different studies are also covered with great details in this book. The book makes physicians able to clearly understand on a scientific basis if their oncologic patients or patients at risk of cancer could actually benefit from a diet enriched in omega-3 PUFAs or from a dietary supplementation with these fatty acids. The book represents also a good resource for ordinary individuals as well as cancer patients to learn more about omega-3 PUFAs and understand how these dietary components may effect cancer growth.
Possible Mechanisms of ?-3 PUFA Anti-tumour Action -- Possible Mechanisms of ?-3 PUFA Anti-tumour Action -- ?-3 PUFAs and Colon Cancer -- ?-3 PUFAs and Colon Cancer: Epidemiological Studies -- ?-3 PUFAs and Colon Cancer: Experimental Studies and Human Interventional Trials -- ?-3 PUFAs and Hormone-Related Cancers (Breast and Prostate) -- ?-3 PUFAs and Breast Cancer: Epidemiological Studies -- ?-3 PUFAs and Prostate Cancer: Epidemiological Studies -- ?-3 PUFAs: Interventional Trials for the Prevention and Treatment of Breast and Prostate Cancer -- ?-3 PUFAs, Breast and Prostate Cancer: Experimental Studies -- ?-3 PUFAs and Other Cancers -- ?-3 PUFAs and Other Cancers -- The Influence of ?-3 PUFAs on Chemo- or Radiation Therapy for Cancer -- ?-3 PUFAs and Cachexia.
Keywords: Medicine; Oncology; Nutrition; Biomedicine; Cancer Research; Oncology; Nutrition